Parricide in the United States, 1840 - 1899 - Segrave, Kerry (McFarland & Company, Inc.)
Sons, fathers, and family abuse -- Sons, fathers, and alcohol -- Sons, fathers, and money -- Sons, fathers, and other causes -- Sons, mothers, and alcohol -- Sons, mothers, and money -- Sons, mothers, and other causes -- Daughters and parents -- Multiple killers -- Multiple victims